2005
DOI: 10.1097/00042737-200511000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Total body metabolism of 13C-octanoic acid is preserved in patients with non-alcoholic steatohepatitis, but differs between women and men

Abstract: Though hepatic mitochondrial function might be impaired in patients with NASH, total beta-oxidation of octanoic acid remains normal. Gender-specific metabolic modifications seem to account for significant differences of the cumulative (13)CO(2) recovery in women and men. This may have further consequences for the appraisal of (13)C breath tests which involve octanoic acid. Further trials focusing on the assessment of body composition and energy expenditure could contribute essential further information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 20 publications
3
35
0
Order By: Relevance
“…Both in vitro and in vivo studies have found no difference in hepatic mitochondrial oxidative capacity between subjects with NAFLD and control subjects, whereas defects in oxidative phosphorylation may be present in nonalcoholic steatohepatitis (NASH) (15)(16)(17)(18)(19). Plasma ketone concentrations have been shown to be higher in subjects with NAFLD and NASH (15), which is indirect evidence of increased hepatic fatty acid oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Both in vitro and in vivo studies have found no difference in hepatic mitochondrial oxidative capacity between subjects with NAFLD and control subjects, whereas defects in oxidative phosphorylation may be present in nonalcoholic steatohepatitis (NASH) (15)(16)(17)(18)(19). Plasma ketone concentrations have been shown to be higher in subjects with NAFLD and NASH (15), which is indirect evidence of increased hepatic fatty acid oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…For the 13 C-based breath tests, pitfalls include potential loss of accuracy in patients with other diseases involving the intestinal mucosa, pancreas, liver, and respiratory system. [ 13 C]octanoic acid is absorbed across the mucosa undigested, so it is not dependent on biliary and pancreatic secretions or mucosal enzymes; moreover, the oxidative break- (105,132). [ 13 C]octanoic acidbased GEBT may be affected by diseases reducing the absorptive capacity of the small intestine and advanced pulmonary disease.…”
Section: Stable Isotope Breath Testsmentioning
confidence: 99%
“…A recent investigation suggested that the total 13 CO 2 recovery in OBT was about 1·3-fold larger in women than in men [21]. A recent investigation suggested that the total 13 CO 2 recovery in OBT was about 1·3-fold larger in women than in men [21].…”
Section: Discussionmentioning
confidence: 98%